Roles of Transmembrane Protein 119 in the Effects of Transforming Growth Factor-β on Mouse Bone Cells - Yamada, Ayaka; Kawao, Naoyuki; Mizukami, Yuya; Kaji, Hiroshi (Experimental and Clinical Endocrinology & Diabetes, 2025)
Transforming growth factor-β (TGF-β), a local growth factor, is essential for bone remodeling; when administered in bone tissues, it stimulates bone formation. On the other hand, transmembrane protein 119 (Tmem119) is a crucial factor for osteoblastic bone formation related to the TGF-β signaling molecule, Smad3. However, the role of Tmem119 in TGF-β-mediated effects on osteoblasts and osteoclasts remains unclear.The function of Tmem119 in TGF-β-mediated effects was examined for osteoblastic differentiation, bone matrix protein expression, and osteoclast formation in mouse osteoblasts, adipose tissue-derived stromal cells, and bone marrow cells from wild-type and Tmem119-deficient mice. Tmem119 deficiency significantly reversed the TGF-β-induced expressions of type I collagen and matrix-Gla protein (MGP) in mouse osteoblasts but did not affect TGF-β-suppressed alkaline phosphatase activity in mouse adipose tissue-derived stromal cells, even when TGF-β could suppress alkaline phosphatase (ALP) activity in mouse osteoblasts regardless of Tmem119 deficiency. Tmem119 deficiency significantly reduced osteoclast formation and Nuclear factor of activated T-cells, cytoplasmic 1 (NFATc1) mRNA levels in mouse bone marrow cells.Tmem119 is involved in regulating type I collagen and MGP expressions and TGF-β-induced osteoclast formation, but does not affect TGF-β-suppressed osteoblastic differentiation in mouse cells.
Keywords: TGF-β; Tmem119; osteoblast; osteoclast